Short Communication: Morphological characterization of five species of Dendrobium native to Indonesia for parent selection - SRI HARTATI; SAMANHUDI SAMANHUDI; ONGKO CAHYONO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Hartati S, Samanhudi, Cahyono O. 2022. Short Communication: Morphological characterization of five species of Dendrobium native to Indonesia for parent selection. Biodiversitas 23: 2648-2654. As one of the most plentiful orchid genera, Dendrobium has a potential genetic resource for crossing programs. Morphological characterization is an important step in determining genetic relationships among orchid species in the same genus. The research aims to identify the morphological characteristics of five species of Indonesian Dendrobium in order to assess the potential cross elder candidates. The materials used in this study were D. mirbelianum Gaudich., D. lamellatum (Blume) Lindl., and D. anosmum obtained from Bogor Botanic Gardens; and D.bracteosum Rchb.f. and D. purpureum obtained from Klaten Speci Gardens. This study recorded 30 morphological characters of Dendrobium studied. There were 23 out of the 30 identified morphological characters (76.67%) that showed varying characters in flowers, leaves, pseudobulbs, and roots. Based on the cluster analysis, five species of Dendrobium are separated into two clusters and cluster division does not correlate with the section of Dendrobium. The species with the highest similarity coefficient has the potential to be used as parental in crosses. Dendrobium lamellatum and D. anosmum have the highest similarity coefficient of 0.80 and are the most potential as parental species for crossing, followed by D. bracteosum and D. purpureum with a similarity coefficient of 0.70.